2016
DOI: 10.1007/s11104-016-3062-3
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with a Pb-tolerant strain of Paxillus involutus improves growth and Pb tolerance of Populus × canescens under in vitro conditions

Abstract: Aims Ectomycorrhizal fungi can improve poplar growth and tolerance to heavy metal stress, and may be useful during the afforestation and phytoremediation of polluted regions with poplar trees. In this study, we determined the effects of the symbiotic interaction between Populus × canescens trees and Paxillus involutus strains different in their tolerance to lead. Methods In vitro inoculated and non-inoculated plants were treated with 0.75 mM Pb(NO 3 ) 2 . The root colonization rate of the two fungal strains, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…A similar effect of Pb was observed on Pisum sativum by Rodriguez et al [57] and on corn by Nyitrai et al [58]. An increase in the chlorophyll content that was caused by Pb was also confirmed in Populus × canescenc trees [59] and Arabis paniculata [45]. The results presented in the current study also confirmed that the phenomenon of hormesis, which is caused by Pb, was positively correlated with a higher chlorophyll content and that there was no significant difference in the PSII yield compared to the control (Figures 3b, 5 and 6b).…”
Section: Discussionsupporting
confidence: 76%
“…A similar effect of Pb was observed on Pisum sativum by Rodriguez et al [57] and on corn by Nyitrai et al [58]. An increase in the chlorophyll content that was caused by Pb was also confirmed in Populus × canescenc trees [59] and Arabis paniculata [45]. The results presented in the current study also confirmed that the phenomenon of hormesis, which is caused by Pb, was positively correlated with a higher chlorophyll content and that there was no significant difference in the PSII yield compared to the control (Figures 3b, 5 and 6b).…”
Section: Discussionsupporting
confidence: 76%
“…Populus × canescens microcuttings (clones) provided by Prof. Krystyna Bojarczuk of the Institute of Dendrology, Polish Academy of Sciences, were propagated in a modified Murashige and Skoog (MS) agar medium containing 1.5% sucrose, as described previously (Szuba et al 2017). Paxillus involutus isolates were obtained from fruit bodies growing in poplar monocultures and maintained in vitro on agar in a modified Melin-Norkrans medium (MMN; Kottke et al 1987) containing 1% glucose and 0.5% maltose.…”
Section: In Vitro Cultures and Experimental Designmentioning
confidence: 99%
“…ECM symbiosis can lead to altered leaf anatomies or larger leaf sizes (Martins et al 1997) that could increase a plant's photosynthetic abilities. ECM fungi can influence, for example, the N status of leaves, which results in an increase (Reid et al 1983;Hobbie and Colpaert 2003) or decrease (Hobbie and Colpaert 2003;Koele et al 2012;Näsholm et al 2013;Szuba et al 2017) in foliar N concentrations. Thus, these changes may be consequences of leaf proteome modifications by ECM symbiosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al [29] and Makita et al [30] have suggested that C allocated to the belowground parts under P limitation is for hyphal growth, fungal respiration, and other fungal metabolic demands, which could greatly increase the nutrient capturing capability of the plant [31]. Although~20% of the carbon assimilated by the plant was consumed by the fungal symbiont [32], ECM fungi associations might prevent the formation of root hairs and thus inhibit root growth [33][34][35]. This might result in relatively lower C in the belowground parts, and thus more C was allocated aboveground [36].…”
Section: Aluminum Resistance and Biomass Production In Ecm P Massonimentioning
confidence: 99%